Effect of sub-doses of 2,4-D choline salt on the characteristics of cotton fiber - Marques, Ricardo Fagundes [UNESP]; Rodrigues Pinheiro, Guilherme Henrique; Santos Araujo, Prissila Pereira dos; Souza, Rodrigo Marques de; Marchi, Sidnei Roberto de (Univ Federal Ceara, Dept Geol, 2021)
Cotton is considered to be one of the most sensitive crops to the herbicide 2,4-D, however, there are no studies related to the effects of contamination of this herbicide on the fiber quality characteristics of cotton. Thus, the objective of this study was to evaluate the effect of sub-doses of 2,4-D choline salt formulation on the quality characteristics of cotton fiber at different phenological stages. The experimental design was based on randomized blocks, with four repetitions and treatments distributed in a 7 x 3 factorial design, with seven fractions of the mean label dose of the herbicide 2,4-D choline salt formulation (0 (control); 0.4275; 0.855; 1.71; 3.42; 8.55; 17.1 g a.e. ha(-1)), associated with three different phenological stages of cotton: V4, B4 and C4. The lint samples were analyzed by the HVI (High Volume Instruments) equipment to determine the main fiber quality characteristics. No sub-dose of the 2,4-D choline salt herbicide affected the fiber quality variables. Contaminations of 2,4-D choline salt at the V4 and B4 stages of cotton directly influence the visual effects of damage and some quality characteristics of cotton fiber, showing that contamination of the herbicide in the initial stages of plant development drastically compromises the crop. The fiber quality variables of cotton plants in the C4 stage were not influenced by the application of 2,4-D choline salt, with no risk if accidental contamination occurs in this stage.
Keywords: Synthetic auxin; Gossypium hirsutum L.; 2,4-dichlorophenoxyacetic acid; High Volume Instruments